Pengaruh reward dan recognition untuk meningkatkan in role dan extra role behavior karyawan yang dimediasi oleh employee engagement di Petrochina International Jabung Ltd - Shadiq, Annurusshadiq; Rosita, Sry; Aurora Lubis, Tona (Program Studi Ekonomi Pembangunan Fakultas Ekonomi dan Bisnis Universitas Jambi, 2022)
The pupose of this study was to examine and determine the effect of reward and recognition to increase in-role and extra-role behavior of employees mediated by employee engagement at Petrochina International Jabung Ltd. – Jambi. The sample used in as many as 81 respondents. Data collection and the method used is a method with a questionnaire that has been tested for validity and reliability then measured using a likert scale and the hypothesis is then analyzed by Structural Equation Modeling (SEM) based on Partial Least Squares Path Modeling (PLS-SEM) components. The results of statistical analysis prove that direct rewards have an insignificant effect on in-role and extra-role behavior and have no significant effect on employee engagement. Recognition directly has an insignificant effect on in-role and extra-role behavior and has a positive and significant effect on employee engagement. The results of statistical analysis also prove that employee engagement has a positive and significant effect on in-role and extra-role behavior. For the mediating effect of the employee engagement variable, it is proven that employee engagement can mediate the indirect influence relationship between recognition on in-role and extra-role behavior.